Memories of US imperialism narratives of the homeland in Filipino and Puerto Rican homes in the United States - Caronan, Faye C. (2012., 2012)
This article examines how institutionalized histories of the US as a benevolent colonial power are reproduced in Filipino and Puerto Rican homes in the United States, facilitated by parents? adherence to these histories. However, US imperialism is justified differently: in the Philippines, through a narrative of rescue from Spain and the brutality of Japan as well as the gifts of democratic institutions; in Puerto Rico, through a narrative of cultural nationalism that foregrounds cultural independence and displaces the question of political independence. The performance poets in this study developed alternative histories and their associated artistic expressions in college rather than at home.
Includes bibliographical references (pages 363-366).
Keywords: Imperialism; Filipino Americans -- Cultural assimilation; Imperialism -- Social aspects; United States -- Foreign relations -- Philippines